Accelerated Hydrogen Gas Sensing of SnO2 Embedded Polyaniline Nanofibers with Doping Pd or Ag Near Room Temperature (Indian Journal of Engineering and Materials Sciences (IJEMS), 2023)
In the present paper, Ag doped SnO2 embedded Polyaniline (ASP) nanofibers and Pd doped SnO2 embedded Polyaniline (PSP) nanofibers have been synthesized successfully. These nanofibers are prepared through the process of electrospinning. ASP and PSP nanofibers have investigated through XRD, EDAX and SEM. The major peaks of the XRD pattern showed perfect matching with JCPDS 41-1445 and confirm rutile nature of SnO2. Energy dispersive study showed composition of elements constituting ASP and PSP nanofibers. SEM images for different doping concentration of Ag and Pd have been obtained which indicate that nanofibers in the range of 100-700 nm are formed. The diameter distribution of SEM images depicted  that most probable diameter of the nanofibers is in the range of 300-400nm. ASP and PSP showed promising results for detection of hydrogen gas. Percentage sensitivity variation with temperature showed the working temperature of around 35oC for all ASP and PSP nanofibers. Response and recovery studies showed response time and recovery time 12-18 second and 20-32 second respectively. Further Pd doping enhances reactivity of SnO2 nanofibers as compared to Ag doping into SnO2 matrix. PSP nanofibers are more selective to hydrogen gas when compared with other atmospheric gases and vapours. The hydrogen gas sensing is assisted through sensitization of Pd decorated SnO2 surface and hierarchical structure of nanofibers.